Cohomology ring of the brst operator associated to the sum of two pure spinors - Mikhailov, Andrei [UNESP]; Schwarz, Albert; Xu, Renjun (World Scientific Publishing, 2013)
In the study of the Type II superstring, it is useful to consider the BRST complex associated to the sum of two pure spinors. The cohomology of this complex is an infinite-dimensional vector space. It is also a finite-dimensional algebra over the algebra of functions of a single pure spinor. In this paper we study the multiplicative structure. © 2013 World Scientific Publishing Company.
Keywords: Cohomology; Pure spinor; Supergravity; Superstring